Influence of Cr and Fe on magnetic phase transition and magnetocaloric effect in Co2(Cr1-xFex)Al, (x ≤ 0 ≤ 1) soft magnetic Heusler alloys. (4th March 2019) - Srivastava, Yogesh; Rathod, Srinivas; Srivastava, Sanjay
ABSTRACT: The structural measurement indicates that the system possesses A2 to B2 phase transformation at the extent of A2 phase at room temperature. The present system shows first order magneto-structural transformation (FOMST). The substitution of Cr by Fe causes a vital role for an increase in magnetocaloric properties. The change in magnetic entropy (ΔSM ) and relative cooling power (RCP) are evaluated under an applied field of 20 KOe that shows drastic changes near the blocking temperature under the specific temperature regime. In the vicinity of these observed properties, critical exponent parameters such as, β, ϒ and δ were also observed using field dependence magnetic entropy change.